Konseling Kelompok Behavioral: Metode Alternatif Meningkatkan Afiliasi Diri - Permatasari, Devi; Latifah, Leny; Kara, Yunita Frederika (JURNAL KONSELING GUSJIGANG, 2023)
Self-affiliation is the need to establish close relationships, make friends and socialize, communicate, work with others, and expect a favorable response from other people or friends. The method used in this research is pre-experimental design. Using purposive sampling technique. The subjects used in this study consisted of 5 students of SMAN 7 Malang class X IPS2, X MIPA5 which were obtained from the results of the self-affiliation pre-test. The instrument used in this study is the self-affiliation scale. Data analysis in this study used Wilcoxon. The results of the study indicate that the technique of modeling behavioral group counseling is acceptable for increasing student self-affiliation.